Mindfulness Practice and Work Performance: The Mediating Role of Emotional Intelligence and Psychological Capital - Hoang Cuu Long; Ho Minh An; Pham Thi Phuong Dung; Nguyen Le Dinh Quy (Brain and Behavior)
ABSTRACT Purpose The practice of mindfulness is becoming more widespread among employees, with potential benefits for workplace outcomes. However, there is a paucity of research on the mechanisms linking mindfulness to job performance. Method This study investigated the mediating functions of emotional intelligence and psychological capital in the relationship between mindfulness and job performance among 263 office employees in Ho Chi Minh City, Vietnam. The “mindfulness‐to‐meaning” viewpoint posits that through the practice of mindfulness, people are able to transcend negative emotions, gain a deeper understanding of themselves, and progress more intentionally by living more consciously in the present moment. Participants completed questionnaires measuring mindfulness, emotional intelligence, psychological capital, and occupational performance. Finding According to the results of structural equation modeling, mindfulness has a direct positive influence on job performance. In addition, emotional intelligence partially mediated the relationship between mindfulness and performance, as evidenced by a greater indirect effect than direct effect. However, the indirect effect via psychological capital was less significant than the direct effect of mindfulness. These findings identify emotional intelligence as a key personal resource that transmits the positive effects of mindfulness on workplace performance. Conclusion The results advance comprehension of intermediary pathways in mindfulness research grounded in the resource‐based view. Integrating emotional intelligence training into mindfulness programs could increase employee productivity in organizations.